(untitled) (Al-Academy, 2025)
(ZnO+CaO +) was used as a low-temperature glaze opacifier as an alternative to common tetravalent oxides (ZrO2, TiO2, and SnO2). The two compounds were added in various proportions to two types of glazes: lead glaze and alkaline glaze. The compounds were applied to a white kaolin body, and the body and glazes were fired at 1000°C. Formula units were calculated using the relationships between the three oxide groups (RO, R2O - R2O3 - RO2). A criterion was established to select the best opacity for the study samples, which was the highest opacity before the glazes hardened. The samples were then microscopically examined to determine the content of the glazes layers, as well as by XRD. It was found that the cause of the opacity was the non-fusion of the added opaque materials, as well as gas bubbles. Colorimetric analysis was then performed using the LAB system, Reflectivity was measured to show the light reflection rate of opaque glazes, and the results were discussed according to scientific data.